A clinical trial of treatment of uncomplicated typhoid fever: efficacy of ceftriaxone-azithromycin combination - Giri, Vishal P.; Giri, Om P.; Srivastava, Anshuman; Mishra, Chandan; Kumar, Ajay; Kanodia, Shubhra (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Typhoid fever is a systemic infection caused by Gram-negative bacterium Salmonella enterica serovar typhi (S. typhi). It is a major health problem in India. It carries significant morbidity and mortality. Antimicrobial therapy is critical for the management of typhoid fever. Emergence of multidrug-resistant (MDR) and nalidixic acid-resistant (NAR) strains of S. typhi has complicated therapy by limiting treatment options. Hence, this study was conducted to evaluate the efficacy and safety profile of ceftriaxone and azithromycin combination therapy in uncomplicated typhoid fever. Methods: Adults patients of blood culture proven uncomplicated typhoid fever admitted in the medicine ward of Teerthanker Mahaveer Medical College and Research Centre were treated with ceftriaxone intravenously (2 g daily for 14 days) and azithromycin orally (500 mg daily for 7 days). Patients were clinically and bacteriologically evaluated during the study period and follow-up. Results: 96% cure rate was observed. No relapse was recorded. Conclusion: Ceftriaxone-azithromycin combination may be considered as an empirical therapy for treatment of uncomplicated typhoid fever in view of the emergence of MDR and NAR strains of S. typhi.